Xylene Isomerization using Hierarchically Mesoporous ZSM-5 - Ahmed El Fadaly; M. A. Sayed; Ahmed O. Abo El Naga; Mohamed El Saied; Seham Ali Shaban; Fouad I. Elhosiny (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
The current study described the synthesis of H-ZSM-5 zeolites with hierarchical micro-meso- porosity (HM-ZSM-5-x) via the soft-templating route, employing organosilane surfactant, 3-[(trimethoxysilyl) propyl]octyldimethyl-ammonium chloride, as the mesoporous template. The catalytic performance was examined in the isomerization of o-xylene in a fixed-bed reactor at atmospheric pressure. Many techniques were conducted to characterize the catalysts. The X-ray diffraction (XRD) and Fourier Transform Infra Red (FTIR) results affirmed that all mesoporous zeolites possess the characteristic MFI structure, as well as good crystallinity. The N2 physisorption measurements signified that all HM-ZSM-5-x samples have higher surface areas and pore volumes than the micro-ZSM-5 sample, with the mesopores accounting for the vast majority of the total surface areas and pore volumes of HM-ZSM-5-x samples. Moreover, the mesoporosity of the obtained HM-ZSM-5-x zeolites can be simply tuned via the variation of the amount of TPOAC used. Compared with classical micro-ZSM-5, the HM-ZSM-5-0.15 sample possessed a higher o-xylene conversion and p-xylene yield that was attributed to its remarkable textural characteristics in terms of higher surface area and prevailing mesoporous character that led to a reduced diffusion limitation. Importantly, the catalyst manifested superb operational stability within 50 h, indicating high resistance against deactivation through coke deposition. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).